The strategies for skills development to upsurge Lesotho’s participation in the textile global value chains: STRATEGIES FOR SKILLS DEVELOPMENT TO UPSURGE LESOTHO’S PARTICIPATION IN THE TEXTILE GLOBAL VALUE CHAINS - Rasethuntsa, Boitumelo Caroline; Mojalefa, Mamoeletsi (Industrija, 2024)
The textile industry plays an essential role towards economic development in the African continent, however, countries such as Lesotho are narrowly participating in the regional textile value chains due to skills gap challenges. The aim of this paper is to identify strategies adopted by four textile leading countries to upscale skills needed in manufacturing enhancement for the industry. Using the literature review approach, this study explores the skills development mechanisms that India, Vietnam, China, and Bangladesh are applying to improve their competitive stand within the global textile industry. The findings of this research indicate that strategies inclusive of public-private collaborations, funding training programmes, engagement of the private sector in training, international partnerships, higher educational institutions collaborations with the textile industry are among other mechanisms that have assisted the four benchmarking countries to integrate more in global textile value chains. The research also provides short-term and medium-term recommendations that decision and policy makers in Lesotho and other African countries can adopt to improve the textile workforce skills so as to take advantage of opportunities in the textile industry regionally and globally.